Leveraging Opportunities: Study on the Resilience Governance Path of Intangible Cultural Heritage Industry in the Context of Online Public Opinion (Journal of humanities and social sciences exploratio, 2026)
The challenges facing intangible cultural heritage (ICH) industries in the contemporary era, characterised by highly fluid information and diverse public value demands, have evolved into systemic propositions involving cultural identity construction, governance capacity enhancement, and social trust maintenance. Resilient governance, with its characteristics of ‘flexible adaptation,collaborative action, and sustained empowerment,’ offers a breakthrough opportunity for mitigating these risks. Drawing upon resilience theory's three-capability model, this study constructs an analytical framework for intangible cultural heritage industry public opinion governance encompassing four resilience dimensions: technical, institutional, subject-based, and cultural.Using the ‘Rongchang Braised Goose Public Opinion Incident’ as a case study, it examines the intrinsic logic and practical pathways of its public opinion governance. Findings reveal that in confronting multiple public opinion shocks, the Rongchang government's successful transition from ‘passive emergency response’ to ‘seizing momentum’ primarily relied on: institutional resilience through establishing an elastic governance system to solidify the foundation of public opinion management; actor resilience by constructing mechanisms for multi-stakeholder collaboration and role reconstruction to consolidate governance synergy; and cultural resilience by reshaping symbolic narratives and value recognition mechanisms to reinforce emotional foundations. Finally, drawing upon the current landscape of public sentiment governance, relevant experiences are summarised across four dimensions-‘technology-institutional-subject-technology’-aiming to provide practical guidance for the intangible cultural heritage industry in navigating public sentiment governance within the era of viral content.
Keywords: Intangible cultural heritage public sentiment governance; Resilient governance; Industrial closed loop; Cultural identity